I have a tendency to love to use the distributive property, so I will show you how to find the answer by doing so.

7(x-1) = -21

7x-7 = -21

7x = -14

x = -2

As you can see, you arrive at the same answer, and I don't think...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

I have a tendency to love to use the distributive property, so I will show you how to find the answer by doing so.

7(x-1) = -21

7x-7 = -21

7x = -14

x = -2

As you can see, you arrive at the same answer, and I don't think it's necessarily any more work.

The equation 7(x-1)=-21 has to be solved for x

7(x-1)=-21

=> x - 1 = -3

=> x = -3 + 1

=> x = -2

**The solution of the equation is x = -2**